Using The RE-AIM Framework to Evaluate A Community-Based Smoke Alarm Installation Program - Stephens-Stidham, Shelli; McCoy, Mary A.; Roper, Carey; Campa, Emily; Barnard, Jeffrey J.; Istre, Gregory R. (Journal of Preventive Medicine And Care, 2016)
We used the five dimensions of the RE-AIM model to evaluate a smoke alarm (SA) installation program called Operation Installation (OI), which was implemented in 36 high risk census tracts in Dallas, TX, from 2001-2011. More than 20,000 SAs were installed in 8,134 houses through OI. The RE-AIM model showed that the program had a modest reach into the target population (26.5%), and a relatively high effectiveness (63%) at preventing deaths and injuries in program houses. Adoption and implementation remained high throughout the time period. Individual level maintenance of SAs was high initially (91.8%), but rapidly declined and was only 20% after 10 years. Application of the RE-AIM model to evaluate this long-term SA installation program highlighted areas that warranted improvement, especially for the dimensions of Reach and individual-level Maintenance. The model may be useful for evaluating the impact of other injury prevention programs.
Keywords: Operation Installation (OI)